İbn Sina’da mead - Kurşunoğlu, Fatma Nuriye (My University, 2006)
“bn Sînâ’da Meâd” adlı tez çalısması, kısaca, Ortaçag slâm filozoflarından bn Sînâ’nın ölümden sonraki hayat ya da ahiret hususundaki görüslerinin ortaya konulmasının amaçlandıgı bir arastırmadır. Çalısma giris ve üç ana bölümden olusmaktadır. Giriste, bn Sînâ öncesi ilkçag Yunan ve Ortaçag slam filozoflarının meâd ya da ölüm sonrası hayat fikirleri, slâm öncesi millî veya semavî dinlerdeki meâd fikri ortaya konulmaya çalısıldı. lk bölüm, bn Sînâ’nın nefs(ruh) görüsü, nefsin varlıgını ispatı, nefsin cisimden ayrı bir cevher olusunu ispatının incelenmesine ayrıldı, Yine bu bölümde düsünürün, nefsin ölümsüzlügünü ispatı ve onun tenasühü (ruh göçünü) reddi ayrıntılı bir sekilde ele alındı. kinci bölümde, bn Sîna’nın cismanî meâd, yanı ölümden sonra bedenin dirilisi fikrine bazı elestirileri yer almaktadır. Üçüncü bölümde ise dünyada yapıp ettiklerine göre, ölümden sonra nefslerin ceza ya da mükâfatları, haz veya elemleri ve mertebeleri hakkında düsünürün fikirleri incelenmektedir. Çalısmada varılan bazı sonuçlar ise sunlardır: bn Sînâ’ya göre insan nefsi ölümden sonra bakidir. Ölüm olayı ile ölen ve dagılan bedendir, nefs ise ölmez. Dinlerde haber verilen bedenin dirilisi fikri ise aklî açıdan ispatlanamamakta, fakat bu fikir düsünürün bazı eserlerinde vahiy bilgisi dogru olacagından, naklî bakımdan kabul edilmektedir. Böyle bir kabul Fârâbî’de bulunmamaktadır. Bu nedenle cismanî hasre inanmamak hususunda bn Sînâ, Fârâbî ile aynı safta ele alınmamalıdır. O, aklî bakımdan bedenin dirilisini ispatlayamasa da, öte dünyada nefslere verilecek ’semavî beden’leri imkânsız görmemektedir. The Thesis workout called “Hereafter in Avicenna ( Ibn Sina )” is briefly a workout aiming to put forward the medieval philosopher Ibn Sina`s beliefs regarding life after death or hereafter. The workout consists of an introduction and three main parts. In the introduction the thoughts of philosophers, who lived before Avicenna (Ibn Sina) in the ancient times and in the medieval age, about life after death or hereafter and the hereafter notion in the pre-islamic national and celestial religions are tried to be put forward. The first part is parted for Avicenna´s (Ibn Sina`s) soul idea, the confirmation of the soul`s existence and the proof of the soul`s being another essence from the object. In addition to that the philosopher`s confirmation of the soul`s immortality and his refusal of its immigration are discussed in a detailed way in this section. In the second part, there are some criticism over Avicenna´s (Ibn Sina`s) corporeal hereafter, in other words, his belief in the body`s resurrection after death. In the third part, the philosopher`s ideas regarding the souls punishment or rewardment after death according to what they did in the world and his thoughts about pleasure or anguish and their stages are analysed. The conclusions that have been arrived in the workout are these: According to Avicenna (Ibn Sina) the human soul is everlasting after the body`s death. With the death event the thing which dies and scatters is the body, the soul does not die. The soul`s resurrection, which is announced within the religions, cannot be proved mentally, however in the philosopher`s some works this thought is accepted in a transferred way since the apocalypse information is right. Such an acceptance is not considered in the thoughts of Al-Farabi. Because of this in the matter of not believing corporeal Day of Judgement, Avicenna (Ibn Sina) should not be considered in the same category with Al-Farabi. Even if Avicenna (Ibn Sina) could not prove the body`s resurrection from the mental way, he does not accept the celestial bodies, which will be given to the souls in the other world, as impossible.
Keywords: İbn Sina; İslam Felsefesi